Nutrition Counseling Gaps in an Adolescent Population in Rural West Virginia - Paige A. Poffenberger; Linda S. Nield; Emily K. Nease; Lesley Cottrell; Melody Phillips; Amna Umer (American Journal of Lifestyle Medicine, 2026)
Adolescents have been identified as a population that receives inadequate nutrition counseling. Medical education for physicians and global policy implementation have aimed to improve this gap. The purpose of this study is to evaluate the effectiveness of these interventions by surveying families with adolescents in rural West Virginia (WV) regarding the nutrition counseling they are receiving at annual physician visits. Surveys were developed based on the US Centers for Disease Control and Prevention (CDC) Guidelines for Americans 2020-2025 to assess how often adolescents’ physicians discussed nutrition topics during their annual visits. Inclusion criteria included families who had an adolescent in their household aged fourteen to eighteen years. These were distributed at two free food pantries in Morgantown, WV. At least 37% of families reported “never” discussing the 10 survey topics with their physician at annual visits. Counseling on limiting saturated fats and sodium intake was most often reported as “never” having been discussed. Despite emerging global policy and medical school interventions to improve nutrition education for physicians, the adolescent population in the studied community is likely not receiving adequate counseling. This highlights the need for practical, scalable strategies to be implemented in the clinical setting.